It's rodeo time, folks! - McWilliams, C.S. (Cimarron, New Mexico Cimarron Legend, 1992)
Article on the Rodeo in Cimarron July 2, 1992.
Master List item #22
File location is in the Raton File Cabinet
Keywords: Hooper, Kaycee; Wiseman, Ron; Sink, Levon; Wayne, Roger; Werhane, G.D.; Wiseman, Judy; Wiseman, Amber; Butler, Don; Mitchell, Wes; Maverick Clubs; 4-H Rodeo; Wiseman Rodeo Company Inc; Philmont Camp; Local History; Rodeo; Roping; Judging; Bull Riding; Rodeo Clown; Young Cowboys/Cowgirls; Scholarship; Cimarron, New Mexico; Clayton, New Mexico